Key Issues in Addressing Trafficking in Women and Children in Nigeria - Chioma Okeoma Okoye; Enright Que Okolie; Anslem Uchechukwu Abonyi (Journal of Gender and Millennium Development Studies, 2025)
Background: Human trafficking, particularly involving women and children, remains a pervasive and deeply rooted issue in Nigeria. Despite existing laws and interventions, systemic weaknesses continue to hinder effective responses to trafficking. Objective: This study examines the key socio-economic, legal, and institutional challenges that impede efforts to combat human trafficking in Nigeria, with a focus on women and children. Method: A qualitative research approach was adopted, utilizing document analysis. Data were drawn from policy documents, official reports, and academic literature. Sources included government agencies, international organizations, and non-governmental organizations. The data were analyzed using a thematic review framework to ensure depth and integrity. Result: The study found that corruption, official complicity, and poor law enforcement are major obstacles to anti-trafficking initiatives. Other contributing factors include inadequate victim support systems, social stigma, cultural barriers, legal loopholes, and weak border control. Socioeconomic drivers such as poverty and unemployment further increase vulnerability to trafficking. Additionally, the misuse of technology has facilitated more complex trafficking networks, while limited international cooperation and insufficient funding continue to undermine progress. Conclusion: Combating human trafficking in Nigeria requires comprehensive legal reform, stronger institutional accountability, enhanced support for victims, robust public awareness campaigns, and greater international collaboration. A coordinated and sustainable national strategy is essential to address the multifaceted nature of the problem. Contribution: This study offers critical insights into the structural and systemic drivers of human trafficking in Nigeria and provides practical policy recommendations for enhancing the effectiveness of anti-trafficking efforts at both national and international levels.